2019
DOI: 10.1080/02656736.2018.1564843
|View full text |Cite|
|
Sign up to set email alerts
|

Nonresective treatments for uterine fibroids: a systematic review of uterine and fibroid volume reductions

Abstract: Patients are increasingly seeking uterus-preserving, minimally invasive treatments for symptomatic uterine fibroids. This has led to a greater use of nonresective treatments such as uterine artery embolization (UAE), focused ultrasound (FUS) and more recently, radiofrequency ablation (RFA) of fibroids. This systematic review, following PRISMA guidelines, examines the change in uterine and fibroid volumes associated with UAE, FUS, and RFA. Pubmed and MedlinePlus databases were searched from 1956 to 2016. The ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…In comparison with other non-interventional techniques, reduction in volume was observed after HIFU (34% ± 8%) than other techniques at 24 months follow-up (UAE 70% ± 11% and RFA (83% ± 8%) [34]. This difference with the aforementioned studies could be attributed to the fact that the initial fibroid volume was higher in the UAE and HIFU groups (UAE: 208.32 ± 112.41, HIFU 209.98 ± 77.83, RFA 84.35 ± 85.06).…”
Section: Fibroid Volume Reductionmentioning
confidence: 70%
“…In comparison with other non-interventional techniques, reduction in volume was observed after HIFU (34% ± 8%) than other techniques at 24 months follow-up (UAE 70% ± 11% and RFA (83% ± 8%) [34]. This difference with the aforementioned studies could be attributed to the fact that the initial fibroid volume was higher in the UAE and HIFU groups (UAE: 208.32 ± 112.41, HIFU 209.98 ± 77.83, RFA 84.35 ± 85.06).…”
Section: Fibroid Volume Reductionmentioning
confidence: 70%
“…77,122,123 According to the location, they are classified as submucosal, intramural and subserosal leiomyomas. 123 Uterine fibroids may be asymptomatic and symptomatic in approximately 50% of cases 140 and present by abnormal uterine bleeding, abdominal or low back pain, painful coitus, urgent urination, urinary frequency, retention of urine and gastrointestinal disorders. 141,142 Risk factors of uterine fibroids are advanced age, hormone, obesity, race, early onset of menarche, nulliparity and same lesion familiar history.…”
Section: Endometriosismentioning
confidence: 99%
“…Sandberg et al 11 reported a reintervention rate of 0.3% at 1 year and 10.4% at 3 years, reductions in SSS of 37 points at 1 year, and increases in HRQL of 35 points at 1 year after laparoscopic RFA. Taheri et al 12 published a review comparing uterine artery embolization, various routes of RFA, and focused ultrasound and found that RFA provided a significantly greater percentage of fibroid volume reduction compared with the other treatments. No previous report has analyzed aggregate outcomes of transvaginal RFA or TFA studies.…”
Section: Figmentioning
confidence: 99%